Acute Vibration Induces Transient Expression of Anabolic Genes in the Murine Intervertebral Disc. Issue 7 (2nd July 2013) - McCann, Matthew R.; Patel, Priya; Beaucage, Kim L.; Xiao, Yizhi; Bacher, Corey; Siqueira, Walter L.; Holdsworth, David W.; Dixon, S. Jeffrey; Séguin, Cheryle A.
<x xml:space="preserve">Abstract</x> Objective Low‐amplitude whole‐body vibration has been adopted for the treatment of back pain and spinal disorders. However, there is limited knowledge of the impact of vibration on the intervertebral disc (IVD). This study was undertaken to examine the effects of acute vibration on anabolic and catabolic pathways in the IVD and to characterize the dependence of these changes on time and frequency. Methods Custom‐designed platforms were developed to apply acute vibration to ex vivo and in vivo mouse models. Spinal segments (ex vivo) or mice (in vivo) were subjected to vibration (for 30 minutes at 15–90 Hz with peak acceleration at 0.3g), and IVDs were examined at specific time points after vibration. Gene expression was quantified using real‐time polymerase chain reaction, and protein levels were examined by quantitative mass spectrometry and immunofluorescence. Results In the ex vivo model, acute vibration at 15 Hz induced expression of anabolic genes (aggrecan, biglycan, decorin, type I collagen, and Sox9) and suppressed expression of Mmp13, with the most pronounced changes detected 6 hours following vibration. These beneficial effects were frequency dependent and were no longer evident between 45 and 90 Hz. In vivo, the effects on anabolic gene expression were even more robust and were accompanied by decreased expression of Adamts4, Adamts5, and Mmp3. Moreover, significant increases in the protein levels of aggrecan, biglycan, decorin, and type I collagen were detected in vivo. Conclusion These findings demonstrate dramatic anabolic effects of acute vibration on IVD tissue, responses that are dependent on frequency. The similarity of the in vivo and ex vivo responses indicates that at least some effects of vibration are tissue autonomous.